Photocurrent generation with two-dimensional van der Waals semiconductors. (7th June 2015) - Buscema, Michele; Island, Joshua O.; Groenendijk, Dirk J.; Blanter, Sofya I.; Steele, Gary A.; van der Zant, Herre S. J.; Castellanos-Gomez, Andres
<x xml:space="preserve">Abstract</x> We review photodetectors based on transition metal dichalcogenides, novel van der Waals materials, black phosphorus, and heterostructures.